The Fear of COVID-19 Pandemic Effects on Couples' Relationship and Sexual Quality of Life Female: A Study from Iran - Rasekhjhroomi, Athar; Ahmadi, Zahra; Ranjbar, Afsaneh; Rahmanian, Vahid; Adedi, Parvin; Mohamadi, Solmaz; Jamali, Safieh (Current Women's Health Reviews, 2025)
BackgroundThe enduring COVID-19 pandemic has implications for the sexual well-being of diverse populations, notably women. This worldwide emergency persists in affecting daily routines of individuals, as research indicates that alterations in lifestyle and imposed limitations are linked to mental health challenges.AimThe objective of this research is to examine the interpersonal dynamics of couples and the sexual well-being of women in the aftermath of the COVID-19 pandemic.MethodsThis cross-sectional research involved 395 female participants who utilized Google Forms to complete online questionnaires in Iran from November 2022 to December 2022. The data collection instruments comprised the Sexual Quality of Life-Female (SQOL-F) questionnaire, Depression Anxiety Stress Scale (DASS), Relationship Rating Scale (RAS), and Fear of COVID-19 Scale. Statistical analyses employed in the study included independent t-test, one-way ANOVA, Tukey post hoc test, and Univariate and Multiple linear regression.ResultsThe average age of female participants in the study was 31.97 years, with a standard deviation of 9.04. The mean scores for sexual quality of life among women were 64.82 with a standard deviation of 11.93, 18.28 with a standard deviation of 4.48 for DASS, 22.48 with a standard deviation of 4.30 for RAS, and 12.88 with a standard deviation of 3.93 for fear of COVID-19 scale. Univariate linear regression analysis indicated a significant association between the quality of sexual life and fear of COVID-19 (P = 0.001), DASS (P = 0.001), and RAS (P = 0.007). The study found a noteworthy and negative impact of fear related to COVID-19 and DASS on the sexual quality of life of women (P < 0.05).ConclusionThe anxiety stemming from the COVID-19 outbreak seems to have repercussions on the dynamics of romantic partnerships and the sexual well-being of women. Furthermore, the pandemic is associated with heightened levels of anxiety, stress, and depression. It is recommended that further research be undertaken to explore the mental health of women and its implications on their sexual experiences in the aftermath of the COVID-19 crisis.
Keywords: COVID-19 pandemic